Heat and emergency room admissions in the Netherlands - Joris Adriaan Frank van Loenhout; Tefera Darge Delbiso; Anna Kiriliouk; Jose Manuel Rodriguez-Llanes; Johan Segers; Debarati Guha-Sapir (BMC, 2018)
Abstract Background Due to a global warming-related increase in heatwaves, it is important to obtain detailed understanding of the relationship between heat and health. We assessed the relationship between heat and urgent emergency room admissions in the Netherlands. Methods We collected daily maximum temperature and relative humidity data over the period 2002-2007. Daily urgent emergency room admissions were divided by sex, age group and disease category. We used distributed lag non-linear Poisson models, estimating temperature-admission associations. We estimated the relative risk (RR) for urgent hospital admissions for a range of temperatures compared to a baseline temperature of 21 °C. In addition, we compared the impact of three different temperature scenarios on admissions using the RR. Results There is a positive relationship between increasing temperatures above 21 °C and the RR for urgent emergency room admissions for the disease categories 'Potential heat-related diseases' and 'Respiratory diseases'. This relationship is strongest in the 85+ group. The RRs are strongest for lag 0. For admissions for 'circulatory diseases', there is only a small significant increase of RRs within the 85+ age group for moderate heat, but not for extreme heat. The RRs for a one-day event with extreme heat are comparable to the RRs for multiple-day events with moderate heat. Conclusions Hospitals should adjust the capacity of their emergency departments on warm days, and the days immediately thereafter. The elderly in particular should be targeted through prevention programmes to reduce harmful effects of heat. The fact that this increase in admissions already occurs in temperatures above 21 °C is different from previous findings in warmer countries. Given the similar impact of three consecutive days of moderate heat and one day of extreme heat on admissions, criteria for activation of national heatwave plans need adjustments based on different temperature scenarios.